2012
DOI: 10.1177/1420326x12452284
|View full text |Cite
|
Sign up to set email alerts
|

How Do Different Locations, Floors and Aspects Influence Indoor Radon Concentrations? An Empirical Study Using Neural Networks for a University Campus in Northwestern Turkey

Abstract: Indoor radon ( 222 Rn) concentrations were measured at a 10-min interval during October 2011 and January 2012. The monitoring followed a randomised and repeated pattern of experimental design, and was carried out at six faculty buildings of the Abant Izzet Baysal University, on five floor levels and two aspect directions (south vs. north) using an AlphaGUARD P30 Radon Monitor. The University campus area located in northwestern Turkey is near the North Anatolian Fault, a major active right lateral-moving strike… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…It is well known that the soil and bedrock are the main source of radon and, as a consequence, radon levels are higher at ground or below ground floors (rooms closer to the soil) than at first floor or above [8][9][10]. Moreover, it has been observed that the contact with soil affects radon spatial variability among rooms at the same floor, which is higher at ground and underground floors than at upper floors [11].…”
mentioning
confidence: 99%
“…It is well known that the soil and bedrock are the main source of radon and, as a consequence, radon levels are higher at ground or below ground floors (rooms closer to the soil) than at first floor or above [8][9][10]. Moreover, it has been observed that the contact with soil affects radon spatial variability among rooms at the same floor, which is higher at ground and underground floors than at upper floors [11].…”
mentioning
confidence: 99%